Holistic Approach of the Evolution Theory to TNC Genesis - Rybalko Yuliia S. (Bìznes Inform, 2014)
Development of the world economy at the modern stage is characterised with formation of the global model of economic development. Economic evolution theory, from the point of view of its supporters, considers economic development as an irreversible process of growth of complexity, variability and productiveness of production by means of periodical repetition of replacement of technologies, types of products, organisations and institutes, quite surprisingly, insufficiently exhaustively reacted in its development on modern challenges in the form of globalisation and processes caused by a new type of reproduction in the post-industrial society. The article, based on main provisions of the economic evolution theory and modern empiricism, specifies general and specific characteristics of development of trans-national corporations (TNC) and provides an improved justification of periodisation of the TNC evolution. The holistic approach of the economic evolution theory to periodisation of the TNC development and the author’s analysis of stages of establishment of TNC give a possibility to identify specific regularities of this development and formulate the hypothesis on probability of coincidence of stages of TNC development and stages of development of the world currency system in the context of time periods, and also to mark out the tendency of formation of corporations of a new generation – mondialised global compositely combined structures.